Flutter in motion - Cornell, Scott (Manning Publications, 2019)
"Flutter, a ground-breaking cross-platform software development kit created by Google, makes it easier than ever to create highly responsive, secure, beautiful native apps for iOS and Android. Flutter embraces modern design patterns, so its applications are loosely-coupled and easy to scale. And because Flutter compiles Dart code to platform-specific programs with no need for a JavaScript bridge, it's blindingly fast. Flutter's built-in widgets and rich motion APIs make you productive fast, so your Flutter apps are as responsive as they are gorgeous!"--Resource description page